Survivability of microencapsulated lactobacillus acidophilus L A-5 synbiotic icecream - Albert Arockiaraj P (Department of Dairy Science, College of Veterinary and Animal Sciences, 2009)
An experiment was conducted to study the efficiency of microencapsulation to improve the survivability of L. acidophilus LA-5 along with the addition of oligofructose in the formulated synbiotic ice cream. The treatment mixes and ice creams were analyzed for various properties by using standard procedures and compared with the control. It was found that addition of L. acidophilus LA-5 either in free or microencapsulated state has not affected the acidity and pH of the ice cream mix. Microencapsulation of L. acidophilus LA-5 increased the specific gravity of the ice cream mix along with addition of oligofructose. Fat, probiotic and coliform counts of the all the treatment ice cream mix were similar to that of the control. The fat content of all treatment ice creams were similar to that of their ice cream mix. Addition of free or encapsulated L. acidophilus LA-5 has not affected the overrun or whipping ability of ice cream. The pH of ice cream was significantly reduced by L. acidophilus LA-5 in free state rather than in microencapsulated state. Addition of oligofructose and low pH increased the meltdown time of ice cream. The weight per litre of ice cream increased significantly with addition of oligofructose than by addition of L. acidophilus LA-5 in both state. Fat and sugar replacers increased the specific gravity of ice cream mix, weight per litre of ice cream and reduced the whipping ability, overrun and meltdown time. Reduction in probiotic count of ice cream was more pronounced during freezing than hardening and storage. The overall probiotic count in ice cream with microencapsulated form of L. acidophilus LA-5 was significantly higher than the ice cream with free form of L. acidophilus LA-5. Low level of fat content has not affected the survivability of L. acidophilus LA-5 in low fat synbiotic ice cream. Overall sensory acceptance of ice cream with microencapsulated L. acidophilus LA-5 was similar to that of the control. Free form of L. acidophilus LA-5 caused slight acidic or sour flavour in the ice cream. Low fat synbiotic ice cream had lowest sensory acceptability. Cost of production of production of synbiotic ice cream with microencapsulated L. acidophilus LA-5 was more than the control. Addition of microencapsulated L. acidophilus LA-5 did not affect any of the technological parameters of the formulated synbiotic ice cream. Microencapsulation efficiently improved the survivability of L. acidophilus LA-5 in the ice cream and ascribed to it the status of a suitable functional food to deliver the recommended level of probiotics with very good sensory attributes to the consumer.